(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Dalit writings are trauma, suffering, rebellion, agitation, and social progress accounts. Trauma is not just a damaging consequence, but also a survival enigma. As such, the writings of Bama deal with the rebuilding of the self after the traumatic impact. This paper aims to recognize key issues, including Dalit history, colonialism, marginalization, poverty, gender and caste, slavery, religion, and Bama’s Karukku in particular. This novel follows Bama’s creation from an average town girl to a Dalit woman who was dedicated to fighting for the cause of the Dalit community. Her disagreement with formal faith and her return to society shape the critical nerve of this fictional work. It is an effort to split the current norm and discover alternatives to establish one’s personality. It testified to the crimes and sufferings and thereby brought the reader into touch with the victimization. Once reality is known, reparation and justice are needed. As witnesses, we have to make changes.